Global Indonesia. - Gelman Taylor, Jean (Routledge contemporary Southeast Asia series., 2012)
In the 19th century, colonial rule brought the modern world closer to the Indonesian peoples, introducing mechanized transport, all-weather roads, postal and telegraph communications, and steamship networks that linked Indonesia's islands to each other, to Europe and the Middle East. This book looks at Indonesia's global importance, and traces the entwining of its peoples and economies with the wider world. The book discusses how products unique to Indonesia first slipped into regional trade networks and exposed scattered communities to the dynamic influence of far-off civilizations. It focuse.